Description of two new species of Rhodostrophia Hübner, 1823 from China (Lepidoptera, Geometridae) - Cui, Le; Xue, Dayong; Jiang, Nan (Zootaxa, 2019)
Two new species of the genus Rhodostrophia Hübner, 1823, Rhodostrophia reisseri sp. nov. and Rhodostrophia stueningi sp. nov. are described from China. The Chinese species of Rhodostrophia are reviewed. Diagnoses for all discussed Chinese species are provided.